Playing for Keeps : A History of Early Baseball - Goldstein, Warren (Book collections on Project MUSE., 2009)
In the late 1850s, organized baseball was a club-based fraternal sport thriving in the cultures of respectable artisans, clerks and shopkeepers, and middle-class sportsmen. Two decades later it had become an entertainment business run by owners and managers, depending on gate receipts and the increasingly disciplined labor of skilled player-employees. Playing for Keeps is an insightful, in-depth account of the game that became America's premier spectator sport for nearly a century. Reconstructing the culture and experience of early baseball through a careful reading of the sporting press, baseball guides, and the correspondence of the player-manager Harry Wright, Warren Goldstein discovers the origins of many modern controversies during the game's earliest decades. The 20th Anniversary Edition of Goldstein's classic includes information about the changes that have occurred in the history of the sport since the 1980s and an account of his experience as a scholarly consultant during the production of Ken Burns's Baseball.